The Mediation Role of University Environment in the Relationship between Self-Efficacy and Family Environment on Entrepreneurial Education Interest: A PLS-SEM Approach - Puspa Widyastuti; Samsul Hadi; Rihab Wit Daryono; Noorazman Bin Abd Samad (Universitas Muhammadiyah Surakarta, 2023)
The courage to take risks to open a new business has not been fully embedded in most technical education students. One of the influences is low student self-efficacy due to a lack of self-confidence in students who think there is a failure in opening a new business. So this research examines and analyzes in-depth related entrepreneurial interest as measured through self-efficacy, family, and university environment in technical education students. The probability sampling method using a random sampling technique was used in taking a sample of 450 participants in technical education students. The most dominant item in representing the success of entrepreneurial interest is creativity at 84.80%. The weakest construct is the never-give-up construct of 71.50%. The ability of the structural model to explain Entrepreneurial Interest is 61.80%, while the Entrepreneurial Interest variable explains 50.50% of the phenomena predicted in the field. The path analysis test reveals that the three variables influence the interest in entrepreneurship positively and significantly. This study recommends that universities foster an interest in entrepreneurship by providing technical assistance in developing businesses, inviting entrepreneurial speakers, holding industrial visits, and conducting training programs. These steps are expected to foster student interest in entrepreneurship.